2018
DOI: 10.1002/pros.23737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and heritability of benign prostatic hyperplasia and LUTS in men aged 40 years or older in Zhengzhou rural areas

Abstract: Background: Benign prostate hyperplasia (BPH) is the most common disease among aging males, but no reports have addressed the prevalence of BPH in Zhengzhou. Therefore, we aimed to understand the prevalence of BPH in men aged 40 years or older in Zhengzhou's rural areas through a cross-sectional study and analyzed the correlation with epidemiologic factors and the heritability of the disease. Materials and Methods:A multistage sampling method was used to randomly select male respondents in Zhengzhou's rural ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Age remains one of the key risk factors of LUTS/BPH in aging population of China. Latest research in rural areas of Zhengzhou, Henan Province, China, indicates the overall prevalence of BPH is 10.04% ranging from 2.17% aged 40-44 years to 31.11% aged 80 years above [24]. Our study also indicates participants suffer higher odds of LUTS/BPH in pace with aging.…”
Section: Discussionsupporting
confidence: 56%
“…Age remains one of the key risk factors of LUTS/BPH in aging population of China. Latest research in rural areas of Zhengzhou, Henan Province, China, indicates the overall prevalence of BPH is 10.04% ranging from 2.17% aged 40-44 years to 31.11% aged 80 years above [24]. Our study also indicates participants suffer higher odds of LUTS/BPH in pace with aging.…”
Section: Discussionsupporting
confidence: 56%
“…It is one of the common diseases in middle-aged and elderly men, and causes a huge burden (Saigal and Joyce, 2005; Speakman et al, 2015). An epidemiological survey on BPH in rural areas in Zhengzhou (a city in central China) showed that the prevalence of BPH was 10.04%, and with age increasing this figure increased from 2.17% in individuals aged 40–44 years to 31.11% in those 80years or older (Yue et al, 2019), which were consistent with findings from a meta-analysis (Wang et al, 2015b) and a survey in Europe (Foster et al, 2015). Main clinical symptoms refer to LUTS, including frequent micturition, urinary urgency, urination inability, trouble in urination starting, etc (Martin et al, 2011; Ho et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…According to one recent study, the prevalence of LUTS/ BPH in aging Chinese males is 11.97%, and is 22.70% in participants aged 70 years old and above (3). Yue et al reported that the prevalence of BPH ranges from 2.17% in men aged 40-44 years to 31.11% in men aged 80 years and above (4). In America, this disease affects an estimated 15 million men aged 30 years and older (5).…”
Section: Introductionmentioning
confidence: 99%